2018
DOI: 10.5830/cvja-2018-013
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators, context of and barriers to acute coronary syndrome care at Kenyatta National Hospital, Nairobi, Kenya: a qualitative analysis

Abstract: SummaryBackgroundThe prevalence of ischaemic heart disease and its acute manifestation, acute coronary syndrome (ACS), is growing throughout sub-Saharan Africa, including Kenya. To address this increasing problem, we sought to understand the facilitators, context of and barriers to ACS care at Kenyatta National Hospital, with the aim of improving the quality of care of ACS.MethodsWe conducted in-depth interviews with healthcare providers involved in the management of ACS patients from January to February 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This data would have led to a better assessment of the appropriateness of the clinical diagnoses and treatments given to enrolled patients, particularly among those diagnosed with ACS. With regards to predictors of decision to obtain an ECG, recent qualitative studies from Tanzania and Kenya found that cost of diagnostic investigations was perceived by providers as an important barrier to ACS care [4,14]. Thus, consideration of patients' financial capacity may have played a significant role in the decision to obtain an ECG.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This data would have led to a better assessment of the appropriateness of the clinical diagnoses and treatments given to enrolled patients, particularly among those diagnosed with ACS. With regards to predictors of decision to obtain an ECG, recent qualitative studies from Tanzania and Kenya found that cost of diagnostic investigations was perceived by providers as an important barrier to ACS care [4,14]. Thus, consideration of patients' financial capacity may have played a significant role in the decision to obtain an ECG.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite such estimates, ACS remains a rare diagnosis across SSA [2,13], a fact that has perplexed epidemiologists [17,26]. Some have speculated that the disease may be under-diagnosed due to a combination of limited community awareness of ACS, inadequate clinician training, and lack of diagnostic equipment [4,14,26].…”
Section: Introductionmentioning
confidence: 99%
“…This is an update from our PROSPERO protocol that was published in 2015 [ 16 ], in which we have included publications between 2015 and December 2020. As a result of re-running our search strategy, we ended up with 439 de-duplicated records, and 14 additional publications after exclusions were made by title and abstract, and subsequently by full text [ [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ] (see Table 3 ). Review for inclusion of articles was conducted independently by two members of the team, and ratified by a third reviewer, as previously detailed in the methods section of the paper.…”
Section: Update 1/2021mentioning
confidence: 99%
“…However, the definitive treatment of reperfusion therapy for STEMI cases, was only conducted in 33% of those that were eligible. Bahiru et al also conducted a qualitative study to understand facilitators and barriers to ACS care at KNH assessing healthcare providers and healthcare leaders involved in their management [ 57 ]. They found themes on: delays in presentation (attributed to lack of patient understanding of ACS symptoms) and delays in inter-hospital transfers.…”
Section: Update 1/2021mentioning
confidence: 99%
“…10 Recent studies among the general population from Tanzania, Kenya, and South Africa have demonstrated that MI is frequently misdiagnosed and not treated according to evidence-based guidelines due to inadequate provider training, lack of awareness among patients, and a lack of diagnostic equipment. [11][12][13][14] Despite an elevated risk of MI in PLWH, few studies probe specific barriers to MI care among this population in SSA.…”
Section: Introductionmentioning
confidence: 99%